Expression of angiopoietin-like protein 2 in ovarian tissue of rat polycystic ovarian syndrome model and its correlation study - Dandan Wang; Yihong Guo; Shujuan Chai; Ke Shen; Yanchun Li; Ruiqin Zhao (BMC, 2020)
Abstract Background This study investigated the expression of angiopoietin-like protein 2 (ANGPTL2) in the tissues of rat models of polycystic ovary syndrome (PCOS) and its correlation with PCOS. Methods Six-weeks-old female specific pathogen-free rats (n = 60) were divided into blank control, PCOS model, and metformin groups (n = 20/group). After 21 days of metformin intervention, the serum sex hormones, fasting blood glucose, fasting insulin, and insulin resistance (IR) of rats in each group were measured. The mRNA levels of ANGPTL2, Foxol, and Akt in the ovarian tissues were monitored by real-time fluorescence quantitative PCR. Results Compared with the control group, the levels of serum sex hormones, fasting blood glucose, fasting insulin, and IR in the model group showed significant increases, and the levels of ANGPTL2, Foxol, and Akt in the ovarian tissue also showed significant increases. Compared with the PCOS group, the serum sex hormones, fasting blood glucose, fasting insulin, and IR of rats in the metformin group were significantly decreased, and the levels of ANGPTL2, Foxol, and Akt in ovarian tissues also showed significant decreases. Conclusions These findings suggest that ANGPTL2 might participate in the development of PCOS through the PI3K/Akt signaling pathway. Metformin improves IR by reducing the expression of ANGPTL2, thus improving the endocrine environment of PCOS and might change the disease outcome.